ANALISIS STOCK SPLIT TERHADAP LIKUIDITAS SAHAM PERUSAHAAN - Liany Christine Anggasta; Sumani Sumani (Prosiding Working Papers Series In Management, 2018)
Stock split is a corporate action carried out by companies that have gone public to rearrange stock prices so that transactions increase and companies become liquid.This study aims to determine the effect of stock split on stock liquidity as measured by the bid-ask spread variable and trading activity volume in companies listed on the Stock Exchange between 2015-2017. The sample used in this study amounted to 53 companies. The method used in this study is paired t-test for the variable bid-ask spread and Wilcoxon Sign Ranked Test for trading volume activity variables.The conclusion obtained from this study is that there is no significant difference in the bid-ask spread for 5 working days, whereas on 15 working days and 30 working days there is a significant difference. In addition, the trading volume activity variable for 5 working days, 15 working days and 30 working days is a difference between before and after stock split Keywords: stock split, bid-ask spread, trading volume activity, stock liquidity